TRANFORMASI PINDANG IKAN TONGKOL MENJADI NUGGET BERSERAT PANGAN DENGAN PENAMBAHAN AMPAS TAHU, MAIZENA DAN RUMPUT LAUT E. cotonii - Hardoko, Hardoko; Thaufani, Mohammad Ovan; Sulistiyati, Titik Dwi; Puspitasari, Yunita Eka (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2024)
‘Tongkol’ fish boiled (‘pindang’) is one of the traditional processed fish products that is popular in lower middle class communities with various weaknesses such as not being able to be consumed by all groups and age groups and not being widely distributed in the modern market. The aim of this research is to determine the type and concentration of binder that is suitable for transforming ‘tongkol pindang’ and okara into fish nuggets that are acceptable to consumers and of good quality. The research method used is an experimental method carried out in two experimental stages. Phase 1st research was designed using a 2-Factor Completely Randomized Design consisting of the binder type factors of wheat flour (A1) and cornstarch (A2) and the binder concentration factors of 10% (B1), 20% (B2), and 30% (B3) ( b/b) on ‘pindang’ meat and okara. The second stage of the research was designed using a simple completely randomized design with E cottonii seaweed substitution treatment 0% (C1), 15% (C2), 30% (C3), 45% (C4), 60% (C5), 75% (C6 ) for the best binder in stage 1st. The data were analyzed for varians and Tukey's test using SPSS 24. The results showed that the type and concentration of treatment had a significant effect (p